Eupatorium lindleyanum DC. sesquiterpene fraction F1012-2 regulates p53/NF-κB signaling pathways in human breast cancer - Wang, Xinyu; Xu, Jiajin; Tao, Yixuan; Fan, Xiangrong; Shen, Xintong; Tian, Shasha (Archives of Biological Sciences, 2022)
Paper description: F1012-2 is a novel sesquiterpene lactone isolated from the Chinese herbal medicine Eupatorium lindleyanum, whose regulation is ill-defined in breast cancer progression. We investigated the anticancer activities of F1012-2 on human breast cancer and its effect on the crosstalk between p53 and NF-κB signaling pathways. F1012-2 exhibited an inhibitory effect on triple-negative breast cancer (TNBC), and this is mainly related to the regulation of p53/NF-κB signaling pathways. F1012-2 co-regulated p53 and NF-κB signaling pathways, thus providing multiple targets for therapeutic intervention in TNBC. Abstract: F1012-2, a novel sesquiterpene lactone isolated from the Chinese herbal medicine Eupatorium lindleyanum DC, exhibits an antitumor effect. In this study, we investigated the anticancer activities of F1012-2 on ten human breast cancer lines and demonstrated significantly lower IC50 values for triple-negative breast cancer (TNBC) than for non-TNBC cell lines. The transcription factors p53 and nuclear factor-κB (NF-κB) are important regulators of tumorigenesis. F1012-2 not only depleted mutant p53, but also activated wild-type p53. F1012-2 reduced the expression of phosphorylated p65 and p105 NF-κB family members and coregulated p53, NF-κB members and their dependent targets. To further clarify the key role of p53, lentivirus small hairpin RNA (shRNA) infection was used to knockdown p53 in MDA-MB-231 cells. F1012-2 significantly reduced the inhibitory effect on cell proliferation and apoptosis, while the levels of p53, NF-κB family members and their dependent genes were not significantly different. F1012-2 exhibited a significant antitumor effect and reduced the expression of p53 in MDA-MB-231 xenografts. Taken together, our results show that F1012-2 exhibited an inhibitory effect on TNBC and affected the regulation of p53/NF-κB signaling pathways.